2020
DOI: 10.1007/s00167-020-06194-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes are comparable using free bone block autografts versus allografts for the management of anterior shoulder instability with glenoid bone loss: a systematic review and meta-analysis of “The Non-Latarjet”

Abstract: Purpose Glenoid augmentation using free bone blocks for anterior shoulder instability has been proposed as an alternative to or bail-out for the Latarjet procedure. The purpose of this investigation was to systematically review and compare outcomes of patients undergoing glenoid augmentation using free bone block autografts versus allografts. Methods A systematic review using PubMed, MEDLINE, Embase, and the Cochrane Library databases was performed in line with the PRISMA statement. Studies reporting outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Glenoid bone grafting is primarily used as a salvage procedure or in patients with more severe glenoid bone loss. 9,56 However, a recent randomized controlled trial by Moroder et al 57 found that iliac crest bone graft transfer resulted in similar clinical results as the Latarjet procedure. Additionally, glenoid bone grafting may have several potential advantages over the Latarjet procedure, including its ability to accommodate a greater degree of glenoid bone loss and reduced risk of convulsion-related graft failure in patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glenoid bone grafting is primarily used as a salvage procedure or in patients with more severe glenoid bone loss. 9,56 However, a recent randomized controlled trial by Moroder et al 57 found that iliac crest bone graft transfer resulted in similar clinical results as the Latarjet procedure. Additionally, glenoid bone grafting may have several potential advantages over the Latarjet procedure, including its ability to accommodate a greater degree of glenoid bone loss and reduced risk of convulsion-related graft failure in patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Alternatively, glenoid bone grafting by means of a free graft transfer may be used to reconstruct the anterior aspect of the glenoid. 9 While proponents of using autograft sources, such as iliac crest cite theoretically improved healing rates and a lower cost over allograft, distal tibial allograft has, thus, far proven to reliably match the congruity of the glenoid arc and has demonstrated excellent union rates. [10][11][12][13][14] Humeral-sided bone loss resulting in an "off-track" and/or engaging Hill-Sachs lesion is commonly treated either indirectly with one of the above procedures, or directly by means of a remplissage.…”
Section: Introductionmentioning
confidence: 99%
“… 102 One systematic review by Gilat et al showed that autograft vs. allograft bone grafting had similar efficacy and safety. 103 …”
Section: Anterior/posterior Bone Graftingmentioning
confidence: 99%
“…102 One systematic review by Gilat et al showed that autograft vs. allograft bone grafting had similar efficacy and safety. 103 Indications for bone grafting for anterior shoulder instability: 99 1. Isolated anterior glenoid bone loss between 20-25% 2.…”
Section: Anterior/posterior Bone Graftingmentioning
confidence: 99%
“… 14 Another potential treatment for treating shoulder instability is block bone procedures, which have been reported to be especially successful in the presence of glenoid bone deficiency. 15 In recent years, Latarjet, a coracoid bone block procedure, has gained growing popularity. This procedure involves a non-anatomical transfer of the coracoid process and cojoined tendon to the glenoid neck.…”
Section: Introductionmentioning
confidence: 99%